2020
DOI: 10.18235/0002791
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of Job Training on Labor Market and Skills Outcomes in Chile

Abstract: Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for attribution, and the use of IDB's logo shall be subject to a separate written license agreement between the IDB and the user and is not authorized as part of this CC-IGO license.Following a peer review process, and with previous written consent by the Inter-American Development Bank (IDB), a revised vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The training and employment system in Chile SENCE in Chile has played a pivotal role in the implementation of training programmes in Latin America (Doerr & Novella, 2020). SENCE was established in 1976 through Decree-Law 1.446 and operates under the Ministry of Labour and Social Welfare.…”
Section: The Perfect Matchmentioning
confidence: 99%
“…The training and employment system in Chile SENCE in Chile has played a pivotal role in the implementation of training programmes in Latin America (Doerr & Novella, 2020). SENCE was established in 1976 through Decree-Law 1.446 and operates under the Ministry of Labour and Social Welfare.…”
Section: The Perfect Matchmentioning
confidence: 99%
“…Batchuluun et al (2017) reported that the youth training programs in Mongolia positively promoted the increase of earning and employment in short and medium terms. Doerr and Rafael (2020) revealed that the beneficiaries of the Formacion para el Trabajo (FOTRAB) programme in Chile improved their income in the short term. The programme trained vulnerable men and women aged 18 to 65.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The findings correlate with Barrera-Osorio et al (2020), Batchuluun et al (2017) and Hirshleifer et al (2014) in Colombia, Malaysia and Turkey respectively. However, Doerr and Rafael (2020) revealed that training influenced the employment of youth in Chile in short term.…”
Section: Role Of Start-up Toolsmentioning
confidence: 99%
“…Specifically, the self-employment rate is negatively associated with training incentives in LLMIC and UMIC, though it is only marginally significant in the former, and with internship/apprenticeship programs in UMIC and HIC. The relationship between the self-employment rate and vocational training has been investigated extensively in the literature, which shows either a modest or no significant relationship between them (Grierson 1997;Premand et al 2012;Doerr and Novella 2020). Some of the explanations provided in these studies include the low quality of vocational programs, which do not account for the wide range of complexities related to self-employment; decreasing returns to extensive training programs, as their distortionary effects increase with their size; their suitability only for the short-term unemployed; their high deadweight losses; and the reduced survival of microenterprises in periods of high unemployment.…”
Section: Econometric Analysis Of Labor Market Outcomes With Respect T...mentioning
confidence: 99%